Sutherlandia frutescens ethanol extracts inhibit oxidative stress and inflammatory responses in neurons and microglial cells. - Jinghua Jiang; Dennis Y Chuang; Yijia Zong; Jayleenkumar Patel; Korey Brownstein; Wei Lei; Chi-Hua Lu; Agnes Simonyi; Zezong Gu; Jiankun Cui; George E Rottinghaus; Kevin L Fritsche; et al. (PLoS ONE, 2014)
Sutherlandia frutescens (L.) R.Br. (SF) is a medicinal plant indigenous to southern Africa and used in folk and contemporary remedies for stress, chronic diseases, cancer, and HIV/AIDS. While previous studies have focused on physiological effects of SF on cellular and systemic abnormalities associated with these diseases, little is known about its effects in the brain and immune cells in the central nervous system. Results of this study indicate that ethanol extracts of SF (SF-E) suppress NMDA-induced reactive oxygen species (ROS) production in neurons, and LPS- and IFNγ-induced ROS and nitric oxide (NO) production in microglial cells. SF-E's action on microglial cells appears to be mediated through inhibition of the IFNγ-induced p-ERK1/2 signaling pathway which is central to regulating a number of intracellular metabolic processes including enhancing STAT1α phosphorylation and filopodia formation. The involvement of SF in these pathways suggests the potential for novel therapeutics for stress and prevention, and/or treatment of HIV/AIDS as well as other inflammatory diseases in the brain.